The pragmatic dimension of pronunciation in The Maqamat of Badi’ Al-Zaman Al-Hamdhani - the Maqamat Al-Harziyya as an example - Alketbi, Alia Ali Saeed; Jaafar, Muhammad Hilmi Abdullah (Arab Journal for Sciences and Research Publishing, 2025)
The research explores the theory of performativity and its relationship to pragmatics in the study of language and communication. Performativity theory focuses on language as a communicative tool used in specific contexts, revealing the speaker's stance through their linguistic choices and structures. It also highlights the importance of the relationship between the speaker and the social context in determining the meaning of the text. Through the analysis of Al-Harzi's maqama, it became evident that language is not merely a tool for transmitting information, but also a tool for interaction and influence. The research also showed that the social context plays a crucial role in shaping the meaning of the text and that performativity directly impacts the reading experience. The study emphasized the importance of viewing literary texts as an integrated artistic work that interacts with the reader on multiple levels. The research adopted a critical analytical approach based on three levels: linguistic structure, textual meaning, and communicative function. It also uses theories of enunciation and pragmatics to understand the nature of creative discourse and the role of speech acts in influencing the recipient. Thus, it aims to present a new vision that highlights the depth and authenticity of the Arab literary heritage in light of modern linguistic approaches.Finally, the research concluded with a set of recommendations, including the need for broader comparative studies, the development of new analytical tools, and the integration of performativity and pragmatics concepts into educational curricula.
Keywords: Articulation theory; pragmatics; speech acts; Al-Harziyya Maqama; literary text; Badi' Al-Zaman Al-Hamadhani